Functionalism and punishment in the new Colombian penal system - Bolivar, Gonzalo (Universidad Pedagógica y Tecnológica de Colombia, 2003)
For the author, a sorrow (sentence) turns out to be a determinant element in the configuration of any system of social control, in turn, the instrument of the most rigorous social control that know the modern societies is the criminal law. Of equal form, the type of criminal law, against which one fights against the phenomenon of the diversion shows us the type of society who tries self to agree, it(she,I) is(am) this democratic or totalitarian. Because of it, the problem of the repression is central in the current theory of the State. The peoples(villages) since(as) ours have strained for obtained a society that simultaneously that allows the exercise of the individual freedoms, it(he,she,I) allows(allow) the above mentioned exercise of freedoms inside the frame of a Social State of right, which can give response to his(its,her) expectations of material justice.